(untitled) (Revista de Investigaciones Universidad del Quindío, 2010)
The research project entitled "Study for the design of a productive policy aimed to development, promotion and strengthening of micro, small and medium enterprises (MSMEs) in Pasto” was financed by Research Subdirection of Institucion Universitaria CESMAG within the research line of Business Development. The main objectives of this project were to concert, and design the proposal of a policy to develop, promotion and strengthen of MSME in the municipality of Pasto. The project had the support of public and private entities directly related with entrepreneurial development in the municipality and their participation was through meetings, talks and filling out surveys in the definition of the constituent elements of the development policy for MSMEs. After systematized and prioritized the obtained information it was concluded that the municipally policy of develop of SME should be led by the Mayor´s office and must be guided by principles of integrity, cooperation, flexibility and universality. This research work allowed along with the participants, five fields of action in which people should contribute their efforts in a coherent and collective way. These fields are: environmental, human talent training, marketing, finance and taxes. The most important finding of this study is that coordination between government institutions and the private sector, academic environment and other government agencies is probably the key for successful development of a policy for the development of local MSMEs. The final document contains elements useful for any municipality in Latin America, given their common problems